2017
DOI: 10.1097/md.0000000000008040
|View full text |Cite
|
Sign up to set email alerts
|

Age-adjusted Charlson comorbidity score is associated with the risk of empyema in patients with COPD

Abstract: Patients with chronic obstructive pulmonary disease (COPD) have a higher risk of pneumonia than the general population due to their impaired lung defense. They also have a higher risk of empyema and more comorbidities than patients without COPD. This study aimed to evaluate the risk of empyema in patients with COPD after adjusting for age and comorbidities using the age-adjusted Charlson comorbidity index (ACCI).Data were retrieved from the National Health Insurance Research Database. COPD patients were define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
(20 reference statements)
0
10
0
Order By: Relevance
“…Studies have shown that diabetes and a higher comorbidity index in patients with COPD chestjournal.org are independent risk factors for the development of empyema. 8 The observed increase in the incidence of thoracic empyema may reflect the greater presence of such risk factors in an aging population. The increasing comorbidity as measured according to the CCI would support this theory.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that diabetes and a higher comorbidity index in patients with COPD chestjournal.org are independent risk factors for the development of empyema. 8 The observed increase in the incidence of thoracic empyema may reflect the greater presence of such risk factors in an aging population. The increasing comorbidity as measured according to the CCI would support this theory.…”
Section: Discussionmentioning
confidence: 99%
“…[35] Symptoms such as dyspnoea, sputum, cough, gasping and difficulty breathing always occur in patients with COPD; lung function declines over time, and medication does not fully reverse the airflow limitation. [6, 7] In addition, the inflammation and/or the changes in repair mechanisms that are accompanied by the release of inflammation mediators may induce or aggravate comorbid diseases such as lung cancer, osteoporosis, cardiovascular disease, depression, anxiety, muscle weakness, and diabetes. [8, 9] It is therefore one common condition that is encountered by most COPD patients in primary care settings who need perpetual medical management.…”
Section: Introductionmentioning
confidence: 99%
“…Like our study, they used the CCI to analyze morbidity and mortality risk in their population. They observed an increased incidence over time of thoracic empyema in patients aged 50–70 and postulated that this trend both reflects a change in the etiology of empyema from risk factors affecting a younger or more at risk population (intravenous drug use, tuberculosis) as well as the greater presence of risk factors such as COPD and diabetes – both independent risk factors for empyema development – in the aging population [ 21 ]. Our study likewise had older patients (an average age of 59.44) with significant comorbidities as measured according to the CCI, supporting the changing epidemiological trends reported in Nayak et al [ 20 ]…”
Section: Discussionmentioning
confidence: 99%